SUN’IY INTELEKT TEXNOLOGIYALARNING MATEMATIK MUAMMOLARI VA YECHIMLARI - Ziyadullayev, Asilbek (Xalqaro ilmiy tadqiqot jurnali, 2026)
This article analyzes the main problems that arise in the process of mathematical modeling of artificial intelligence and digital technologies, and considers modern approaches to solving them. The article first explains that artificial intelligence systems are based on simplified mathematical models of real processes. Based on this, the main difficulties such as overfitting of models, data quality problems, computational complexity, algorithmic bias and stability issues are revealed with examples.